A Unique Gene Module in Thermococcales Archaea Centered on a Hypervariable Protein Containing Immunoglobulin Domains - Makarova, Kira S.; Wolf, Yuri I.; Karamycheva, Svetlana; Koonin, Eugene V. (Frontiers in Microbiology, 2021)
Molecular mechanisms involved in biological conflicts and self vs nonself recognition in archaea remain poorly characterized. We apply phylogenomic analysis to identify a hypervariable gene module that is widespread among Thermococcales. These loci consist of an upstream gene coding for a large protein containing several immunoglobulin (Ig) domains and unique combinations of downstream genes, some of which also contain Ig domains. In the large Ig domain containing protein, the C-terminal Ig domain sequence is hypervariable, apparently, as a result of recombination between genes from different Thermococcales. To reflect the hypervariability, we denote this gene module VARTIG (VARiable Thermococcales IG). The overall organization of the VARTIG modules is similar to the organization of Polymorphic Toxin Systems (PTS). Archaeal genomes outside Thermococcales encode a variety of Ig domain proteins, but no counterparts to VARTIG and no Ig domains with comparable levels of variability. The specific functions of VARTIG remain unknown but the identified features of this system imply three testable hypotheses: (i) involvement in inter-microbial conflicts analogous to PTS, (ii) role in innate immunity analogous to the vertebrate complement system, and (iii) function in self vs nonself discrimination analogous to the vertebrate Major Histocompatibility Complex. The latter two hypotheses seem to be of particular interest given the apparent analogy to the vertebrate immunity.